G586(P) Screening for congenital hypothyroidism: a 21-year audit of practice and outcomes from a tertiary uk centre. (May 2019) - Shah, J; Lambert, CR; Goddard, P; Preece, MA; Karthikeyan, A; Barrett, T; Dias, R
Abstract : Aims: The UK newborn screening program facilitates early identification and treatment of Congenital Hypothyroidism (CHT) to prevent neurodevelopmental defects. This study audited practice and outcome data from a regional tertiary centre (RTC) over a 21 year period against the 2013 CHT national screening standards. Data from this centre was compared with the region as a whole between 2014–2017. Methods: Data from infants (n=96), collected from patient records and screening laboratory databases who received treatment at the RTC and screened between 1997–2017, was analysed in four consecutive time periods. Regional screening data between 2014–2017 (n=147) was also compared with RTC data (n=23). Results: Between 1997–2002 and 2013–2017, median age (range) of screening improved from 9 (7–24) to 6 (5–16) days. Median time for repeat sample after borderline results (thyroid stimulating hormone (TSH) concentration 10–20mU/L) improved from 11 (8–15) to 8 (2–13) days. Between 1997–2002 and 2013–2017, median age at starting thyroxine replacement improved from 18 (13–184) to 12 (9–21) days. TSH normalised within 1 month of treatment for 20% of infants in 2013–2017. Between 2008–2012 and 2013–2017, median laboratory reporting time improved from 6 (2–26) to 5 days (3–8) and median time from referral to clinician review improved from 1 day (0–7) to the same day (0–2 days). 100% (11/11) of babies identified after initial screening sample were treated by the recommended 14 days of age at the RTC between 2014–2017, compared with 88% (90/102) in the region as a whole. Conclusion: This was the first retrospective CHT study on this scale in the RTC demonstrating clear improvements in management, likely due to changes in national and local treatment structures including: Earlier clinician review with increased RTC consultant workforce; 1.2 whole time equivalent consultants in 1994 to 6.8 in 2017 Improved analysis and reporting pathway, leading to earlier referrals Clearer local guidance and management of borderline results Improved care pathway including TSH sampling at 2, 4, and 8 weeks Further practice improvements are required including: timing of repeat sample, treatment of borderline results and time to TSH normalisation. These may require further review of the starting dose of thyroxine (currently 10–15micrograms/kg/day).